Irisin alleviated the reproductive endocrinal disorders of PCOS mice accompanied by changes in gut microbiota and metabolomic characteristics - Yang, Meina; Deng, Hongxia; Zhou, Siyu; Lu, Danhua; Shen, Xiaoyang; Huang, Lu; Chen, Yan; Xu, Liangzhi (Frontiers in Microbiology, 2024)
Folliculogenesis and oligo/anovulation are common pathophysiological characteristics in polycystic ovary syndrome (PCOS) patients, and it is also accompanied with gut microbiota dysbiosis. It is known that physical activity has beneficial effects on improving metabolism and promoting ovulation and menstrual cycle disorder in PCOS patients, and it can also modulate the gastrointestinal microbiota in human beings. However, the mechanism remains vague. Irisin, a novel myokine, plays a positive role in the mediating effects of physical activity. In this study, we demonstrated that irisin supplementation alleviated reproductive endocrine disorders of PCOS mice induced by DHEA (dehydroepiandrosterone) and HFD (high-fat diet), including estrous cycle disturbance, ovarian polycystic degeneration, and hyperandrogenemia. Irisin also improved the PCOS follicles dysplasia and ovulation disorders, while it had no significant effect on the quality of oocytes. Moreover, irisin could mitigate the decreased bacteria of Odoribacter and the increased bacteria of Eisenbergiella and Dubosiella in PCOS mice model. What's more, irisin could alleviate the increased fecal metabolites: Methallenestril and PS (22:5(4Z,7Z,10Z,13Z,16Z)/LTE4). These results suggest that irisin may alleviate the status of PCOS mice model by modulating androgeninduced gut microbiota dysbiosis and fecal metabolites. Hence, our study provided evidence that irisin may be considered as a promising strategy for the treatment of PCOS.